Building health: an epidemiological study of "sick building syndrome" in the Whitehall II study. Issue 4 (23rd March 2006) - Marmot, A F; Eley, J; Stafford, M; Stansfeld, S A; Warwick, E; Marmot, M G
Abstract : Objectives: Sick building syndrome (SBS) is described as a group of symptoms attributed to the physical environment of specific buildings. Isolating particular environmental features responsible for the symptoms has proved difficult. This study explores the role and significance of the physical and psychosocial work environment in explaining SBS. Methods: Cross sectional data on the physical environment of a selection of buildings were added to individual data from the Whitehall II study—an ongoing health survey of office based civil servants. A self-report questionnaire was used to capture 10 symptoms of the SBS and psychosocial work stress. In total, 4052 participants aged 42–62 years working in 44 buildings were included in this study. Results: No significant relation was found between most aspects of the physical work environment and symptom prevalence, adjusted for age, sex, and employment grade. Positive (non-significant) relations were found only with airborne bacteria, inhalable dust, dry bulb temperature, relative humidity, and having some control over the local physical environment. Greater effects were found with features of the psychosocial work environment including high job demands and low support. Only psychosocial work characteristics and control over the physical environment were independently associated with symptoms in the multivariate analysis. Conclusions: The physical environment of office buildings appears to be less important than features of the psychosocial work environment in explaining differences in the prevalence of symptoms.